Hepatic Extracellular Matrix and Its Role in the Regulation of Liver Phenotype - Arteel, Gavin E. (Seminars in Liver Disease, 2024)
The hepatic extracellular matrix (ECM) is most accurately depicted as a dynamic compartment that comprises a diverse range of players that work bidirectionally with hepatic cells to regulate overall homeostasis. Although the classic meaning of the ECM referred to only proteins directly involved in generating the ECM structure, such as collagens, proteoglycans, and glycoproteins, the definition of the ECM is now broader and includes all components associated with this compartment. The ECM is critical in mediating phenotype at the cellular, organ, and even organismal levels. The purpose of this review is to summarize the prevailing mechanisms by which ECM mediates hepatic phenotype and discuss the potential or established role of this compartment in the response to hepatic injury in the context of steatotic liver disease.
Keywords: extracellular matrix; matrisome; hepatic; liver disease